Cultivating Prophetic Values in Character Formation - Mulyanto, Tri; Sirait, Sangkot; Sumarni, Sri (Universitas Islam Negeri Raden Intan Lampung, 2023)
This research aims to address the decline in character values that occur in the world of education, this is indicated by the frequent occurrence of immoral acts by students and educators. So that schools provide alternative solutions to overcoming problems by cultivating prophetic values in character building. This study uses qualitative research with an ethnographic approach, namely an approach based on experience and theory that aims to describe and analyze culture in depth. The research subjects included school principals, deputy heads of curriculum, deputy heads of student affairs, Ismuba teachers, and students to dig deeper into information about cultivating prophetic values. While collecting data in this study using observation techniques, interviews, and documentation. The data analysis process of researcher uses data condensation, data display, and verification processes. The validity of the data researchers used data triangulation techniques. The results of this study indicate that the promotion of prophetic values in character building at SMP Muhammadiyah 1 Depok is carried out in two ways, namely through Ismuba education learning activities and cultural programs. Cultivating prophetic values in learning is done by getting used to praying before learning, saying greetings, monitoring the cleanliness of the classroom environment, neatness, and discipline of students, mutual respect, and helping each other. Meanwhile, cultivating school culture is carried out using clean living habits, discipline, responsibility, shame, praying in congregation, helping, Muslim dress, literacy, and enthusiasm for learning. The results of this study have implications for the importance of the commitment of SMP Muhammadiyah 1 Depok personnel to increase the cultivation of prophetic values through exemplary and habituation methods.